2006
DOI: 10.1002/ana.20733
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity networks are disrupted in left temporal lobe epilepsy

Abstract: We suggest that this reduced connectivity in left temporal lobe epilepsy may reflect a disturbance of the language network during resting state in patients and may be related to subtle language difficulties in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
212
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 289 publications
(234 citation statements)
references
References 54 publications
17
212
1
1
Order By: Relevance
“…Differences on connectivity alterations between left and right MTLE have been previously described in the literature [Haneef et al, 2015; Pereira et al, 2010; Waites et al, 2006]. Through diversified methodologies, these studies explored distinct aspects of brain functional connectivity using anatomical or functional relevant ROIs, independent component analysis and graph theoretical information.…”
Section: Discussionmentioning
confidence: 97%
“…Differences on connectivity alterations between left and right MTLE have been previously described in the literature [Haneef et al, 2015; Pereira et al, 2010; Waites et al, 2006]. Through diversified methodologies, these studies explored distinct aspects of brain functional connectivity using anatomical or functional relevant ROIs, independent component analysis and graph theoretical information.…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that changes in functional connectivity can be used as an early marker of some diseases. Decreased correlations have been reported involving the hippocampus of patients with Alzheimer's disease [82;83], the motor cortices and frontal regions of multiple sclerosis patients [84;85], and the left hemisphere language network of left temporal lobe epilepsy patients [86]. Changes in functional connectivity have been detected in patients with schizophrenia [87;88] and attention deficit hyperactivity disorder [89].…”
Section: Intrinsic Variancementioning
confidence: 99%
“…While structural “network disease” is unlikely to explain cognitive impairment in all cases,9 the underlying concept can be expanded to incorporate functional network disease as well. From this perspective some of the cognitive deficits in TLE, and indeed in epilepsy more generally, represent alterations in functional networks 9, 10, 11…”
Section: Introductionmentioning
confidence: 99%